Singular integral inequalities with several nonlinearities and integral equations with singular kernels - Medveď, M. (Нелінійні коливання, 2008)
We deal with an integral inequality with a power nonlinearity in its left-hand side, with n nonlinearities in its right-hand side, and weakly singular kernels. The obtained result is an extention of the Bihari, Henry, Pachpatte and Pinto inequalities and results obtained by the author. Using these results we prove sufficient conditions for existence of global solutions of some nonlinear Volterra integral equations with singular kernels and n nonlinearities.